Using Shields as Educational Tools for Firmware Development on Engineering Courses - Barbosa, Otávio; Dias, Samaherni (Anais do Workshop on Sustainable Computing and Technology Reuse (SCoRe), 2025)
Engineering education demands the integration of theory and practice, yet most commercial kits are costly and limited to specific experiments. This work presents an educational shield compatible with the UNO R3 pin standard to support embedded systems learning. The shield features LCD and 7-segment displays, push-buttons, a buzzer, an RGB LED, a potentiometer, an R-2R ladder network, and interfaces for I 2 C, SPI, and UART protocols, broadening experimentation options. The methodology comprised requirement definition, component selection, schematic design, and PCB development using EasyEDA. The shield enables practical experiments such as digital safes, digital filters (IIR, FIR), Software-Defined Radio (SDR), control systems (PID), timers with Human-Machine Interface (HMI), I 2 C-based schedulers, and spectrum analyzers.